Warisan Spiritual di Tanah Sriwijaya: Upaya Pelestarian Makam Keramat Panjang sebagai Destinasi Wisata Religi - Meysi Wulandari AP; Hudaidah Hudaidah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This research aims to examine the contribution of the Panjang Sacred Tomb site as part of Islamic cultural heritage in Indonesia and the importance of preserving local culture in Palembang City. This research uses a descriptive qualitative method with a field approach. Data collection techniques were conducted through direct observation, in-depth interviews with the caretaker of the tomb and the surrounding community, and visual documentation at the location. The research subjects included tomb managers, pilgrims, and local residents. The main instruments used in this research are interview guidelines and observation sheets. The results show that the Long Sacred Tomb has a significant role in shaping local religious and cultural structures, where the community still preserves the pilgrimage tradition as a form of respect for spiritual figures who are considered meritorious in the spread of Islam in the area. The site also serves as a means of educating religious and cultural values for the younger generation. Therefore, physical and educational preservation efforts are needed on an ongoing basis so that this site remains alive in the collective consciousness of the community and can transform into a religious tourism destination with high educational and cultural power.